The Effects of Species Exposure on Chemical Communication Behavior in Beetles - Alexander, Lindsey; Marshall, Jeremy L. (My University, 2017)
The Tribolium castaneum genome sequence contains a large number of odorant receptor (Or) genes when compared to the olfactory genomes of other insects (Engsontia et al., 2007). Evolved populations of the red flour beetle differ in their ability to detect chemical senses (Boake & Wade, 1984). Red flour beetles have been noted to release compounds via glands on their femurs (Olsson et al., 2006). This study observes the effects of chemical communication on behavior in beetles by comparing the response of the red flour beetles to areas predisposed to the chemical communication of other species. The purpose of this research is to study the effects of chemical communication in beetles by comparing the behavior of beetles exposed to life with only members of their own species to life in a group setting exposed to other species. If members of the species, Tribolium castaneum, were exposed to living with other species of beetles, then these beetles would be more likely to be present in areas predisposed to the other species. When accounting for edge behavior tendencies in beetles, this study observed that 80% of the tested individuals from the single species environment visited the red flour beetle chemical communication patch, while only 50% of individuals exposed to the group of multiple species were found on the patch chemically marked by species of red flour beetles. Results of this study support the notion that living alongside other species likely influences chemical communication preferences in beetles.